IDENTIFIKASI JENIS DAN FAKTOR PENYEBAB KERUSAKAN RIGID BETON PADA BAHU JALAN (STUDI KASUS RUAS JALAN BEUTONG-BEUTONG ATEUH KAB. NAGAN RAYA) - maulana, akbar; Satria, Andrisman; Febrianti, Dian (Journal of The Civil Engineering Student, 2022)
The Beutong-Beutong Ateuh causeway is a path made for the human activity of objects and employment. so that existing transportation activities are greatly influenced by the state of the pavement or road. Moreover, the road is a road that passes through the mountains, of course the most important thing to note is the feasibility of the road for road users. but the shoulder of the road is also no less important for road users, especially on mountain roads. in addition to being a place for vehicles that stop in an emergency, the shoulder of the road also provides side resistance for pavement and also as surface drainage. The purpose of this study is to find out the types of damage and factors that affect damage to the shoulder of the road made of rigid concrete. The method used is direct research of spaciousness, namely the results of a survey of rigid concrete damage on the shoulder of the Beutong-Beutong Ateuh road.Based on the results of research, the type of rigid concrete damage is a diagonal crack( diagonal crack ), winding crack, transverse crack, scalling, break corners, cross cracks or broken plates.